2017
DOI: 10.1002/ece3.2796
|View full text |Cite
|
Sign up to set email alerts
|

Host sharing by the honey bee parasites Lotmaria passim and Nosema ceranae

Abstract: The trypanosome Lotmaria passim and the microsporidian Nosema ceranae are common parasites of the honey bee, Apis mellifera, intestine, but the nature of interactions between them is unknown. Here, we took advantage of naturally occurring infections and quantified infection loads of individual workers (N = 408) originating from three apiaries (four colonies per apiary) using PCR to test for interactions between these two parasites. For that purpose, we measured the frequency of single and double infections, es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 54 publications
4
24
1
Order By: Relevance
“…Co-infection by N. ceranae and L. passim was also previously established in honeybee samples from Switzerland (Tritschler et al, 2017). Infection of both N. ceranae and C. mellificae parasites was described for honeybees from Belgian apiaries (Ravoet et al, 2013) (see Fig.…”
Section: Microsporidian Infectionsupporting
confidence: 52%
“…Co-infection by N. ceranae and L. passim was also previously established in honeybee samples from Switzerland (Tritschler et al, 2017). Infection of both N. ceranae and C. mellificae parasites was described for honeybees from Belgian apiaries (Ravoet et al, 2013) (see Fig.…”
Section: Microsporidian Infectionsupporting
confidence: 52%
“…The thermal conditions were achieved with one cycle at 95 °C for 10 min, followed by 40 cycles at 95 °C for 15 s, 60 °C for 15 s and 72 °C for 15 s. A dissociation analysis was conducted after all of the amplifications were completed in order to detect the primer dimmers and the unspecific amplicons. Thus, the data regarding the pathogen loads were reported as cell or spore equivalents per bee, according to Tritschler et al [ 23 ]. Similarly, the data concerning immune-related genes were reported as relative expressions after normalization with an endogen gene (β-actin), according to Pfaffl [ 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, there is no experimental evidence related to how a mixed infection of N. ceranae and L. passim could affect honey bee colonies. Some current reports have shown that mixed infections of these pathogens are not common (no more than 2%), in spite of the fact that they have been detected in high prevalence in single infections in honey bee hives [ 3 , 23 ], suggesting a possible competition between these two parasites. Furthermore, such mixed-species infections may influence the host immune responses, including genes that elicit antimicrobial peptides (AMPs) [ 7 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…L. passim is the founding member of this genus ( Figure 1 ). This member of Crithidiatae is described as a common parasite of the honey bee Apis mellifera [ 25 ], which calls into question its presence in a human gut microbiome.…”
Section: Resultsmentioning
confidence: 99%